Imperative style (Uslūb Al-Amr) in the Kitāb Al-Arba'īn An-Nawāwiyyah (a semantic analysis) / Afif Muttadin Munir, Yusroh and Yoyo - Munir, Afif Muttadin; Yusroh, Yusroh; Y, Yoyo (2021)
The paper aims to explain the form and meaning of the imperative style in the Kitāb Al-Arba'in An-Nawāwiyyah by Al-Hafizh Abu Zakariya Yahya bin Syaraf An-Nawawi from the perspective of semantic theory. The author uses a descriptive qualitative method combined with a semantics approach to analyse the imperative style's type and meaning in the Kitāb Al-Arba'in An-Nawāwiyyah. The result indicates that there are 27 data on imperative style in the Kitāb Al-Arba'in An-Nawāwiyyah that can be classified based on its type and meaning. From its type and form, there are three kinds of imperative style in the Kitāb, as follows: 1) imperative style in its basic form or ; فعل الأمر 2) imperative style that is preceded by the 'lam al-amr or الفعل المضارع المقرون بلام الأمر ; and 3) imperative style in the form of a noun or اسم فعل الأمر . Meanwhile, from its semantic perspective, there are five meanings of imperative sentence as follows; 1) imperative as guidance إرشاد; 2) imperative as request or دعاء ; 3) imperative as a choice or التخيير; 4) imperative as threat or التهديد , and 5) imperative in its original meaning